A comparison between preterm and full-term infants' preference for faces - Silvana A. Pereira; Antônio Pereira Junior; Marcelo F. da Costa; Margareth de V. Monteiro; Valéria A. de Almeida; Gentil G. da Fonseca Filho; Nívia Arrais; Francesca Simion
Abstract: Objective: Visual preference for faces at birth is the product of a multimodal sensory experience experienced by the fetus even during the gestational period. The ability to recognize faces allows an ecologically advantageous interaction with the social environment. However, perinatal events such as premature birth, may adversely affect the adequate development of this capacity. In this study, we evaluated the preference for facial stimuli in preterm infants within the first few hours after birth. Methods: This is a cross-sectional observational study of 59 newborns, 28 preterm and 31 full-term infants. The babies were assessed in the first hours of life, with two white boards in the shape of a head and neck: one with the drawing of a face similar to the human face (natural face), and one with the drawing of misaligned eyes, mouth and nose (distorted face). After the newborn fixated the eyes on the presented stimulus, it was slowly moved along the visual field. The recognition of the stimulus was considered present when the baby had eye or head movements toward the stimulus. Results: The preterm infants, in addition to showing a lower occurrence of orientation movements for both stimuli, on average (1.8 ± 1.1 to natural faces and 2.0 ± 1.2 for distorted ones) also showed no preference for any of them (p = 0.35). Full-term newborns showed a different behavior, in which they showed a preference for natural faces (p = 0.002) and a higher number of orientations for the stimulus, for both natural (3.2 ± 0.8) and distorted faces (2.5 ± 0.9). Conclusion: Preterm newborns recognize facial stimuli and disclose no preference for natural faces, different from full-term newborns.